ANALISIS KARAKTERISTIK LAHAN DAN MUTU BIJI PALA (Myristica fragrans Houtt) DAERAH LAMPUNG / Analysis of Land Characteristics and Nutmeg (Myristica fragrans Houtt) Seed Quality of Lampung - Bariot Hafif; Rahadian Mawardi; Joko Susilo Utomo (Jurnal Penelitian Tanaman Industri, 2017)
Lampung Province is one of nutmeg-producing region in Sumatra. Today nutmeg is one of the region's export commodities. The quality is an important factor in global nutmeg trade. The aim of this study was to assess nutmeg development prospect by analyzing the land characteristics and the quality of nutmeg. The study utilized a survey method to characterize the land and performance of smallholder nutmeg plantations, to communicate with farmers and to sample some nutmeg seeds for quality analysis. The survey was carried out in four subdistricts of the main nutmeg producing areas in Tanggamus Regency, namely Kota Agung-Timur, Gisting, Semaka, and Air-Naningan, in each area, 2-3 smallholder nutmeg plantations were assessed. The areas suitable for nutmeg development are Kota Agung-Timur, Gisting, and Semaka. The main supporting factor is water availability throughout the year, whereas the limiting factor are air humidity >75%, low organic C and CEC ≤16 cmol (+)/kg of soil, and erosion hazard due to a slope of >15%. Nutmeg productivity has potentials to be improved through technological innovation as current nutmeg cultivation is still conventional and does not use superior seeds, fertilizer and postharvest technology. On the other hand, the nutmeg seeds qualities have met SNI standards such as specific gravity, refractive index, optical rotation, soluble in alcohol, and chemical properties such as myristicin, α-pinene, sabinene, and safrole. Methyl eugenol is below the threshold of the European Pharmacopoeia standard and the α-pinene is better than nutmeg essential oil of produced from other regions.Keywords: nutmeg, land, physical and chemical qualities of nutmeg, Tanggamus of Lampung Province AbstrakProvinsi Lampung adalah salah satu daerah penghasil pala di pulau Sumatera. Saat ini pala merupakan salah satu komoditas ekspor daerah tersebut. Mutu merupakan faktor penting dalam perdagangan pala global. Tujuan penelitian adalah mengkaji prospek pengembangan tanaman pala berdasarkan analisis karakteristik lahan dan mutu hasil pala di Provinsi Lampung. Penelitian menggunakan metode survei untuk mengkarak-terisasi lahan dan keragaan tanaman pala, serta melakukan tanya jawab dengan petani dan mengumpulkan biji pala untuk bahan analisis mutu. Survei dilaksanakan di empat daerah penghasil pala utama di Kabupaten Tanggamus, yaitu Kecamatan Kota Agung Timur, Gisting, Semaka dan Air Naningan. Di masing-masing kecamatan dikunjungi 2 - 3 kebun pala rakyat. Daerah yang cukup sesuai untuk pengembangan pala adalah Kota Agung Timur, Gisting, dan Semaka (Tanggamus bagian Barat). Faktor pendukung utama pertumbuhan dan produksi pala di daerah ini ialah air tersedia sepanjang tahun, sedangkan faktor pembatas adalah kelembapan udara >75%, kandungan C-organik tanah rendah, dan KTK tanah 16 cmol (+)/kg. Faktor pembatas lainnya adalah bahaya erosi tinggi yang disebabkan oleh kemiringan lahan >15%. Produksi dan mutu pala berpotensi ditingkatkan melalui inovasi teknologi karena budidaya pala masih bersifat konvensional, tanpa bibit unggul, pupuk dan teknologi pascapanen. Potensi lain adalah sifat fisik seperti berat jenis (BJ), indeks bias, putaran optik, kelarutan dalam alkohol, dan sifat kimia seperti kandungan miristisin, -pinen, sabinen, serta safrol biji pala Lampung telah memenuhi SNI. Metil eugenol sebagai senyawa karsinogenik terukur di bawah ambang batas ketetapan European Pharmacopoeia, dan kandungan -pinen terindikasi lebih baik dibanding di dalam minyak atsiri biji pala daerah lainnya di Indonesia.Kata kunci: pala, lahan, mutu fisik dan kimia pala, Tanggamus Provinsi Lampung